The acceptance factors of UiTM WESLLAP as an open distance learning platform based on the technology acceptance model / Noor Azli Affendy Lee ... [et al.] - Affendy Lee, Noor Azli; Boon, Yih Mah; Ab Rahim, Suzana; Jamil, Marni (Universiti Teknologi MARA, Sabah, 2021)
The crucial issues for successful technology-enhanced out-of-class language learning are the learners' attitude and the continuance intention to use technology. Hence, when designing and implementing a relevant and innovative e-learning platform, there is a salient need to identify the acceptance factors of users. The Technology Acceptance Model (TAM) has received significant recognition through various research conducted to determine users' acceptance of relevant technology innovations. This paper attempts to describe students' acceptance in using an open access e-learning website, namely UiTM WESLLAP (https://uitmwebitors.wixsite.com/uitmwesllap), for their English proficiency course during the Open Distance Learning (ODL) period in April to July 2020. A set of questionnaires based on TAM was distributed to 72 semester one diploma students before the start of the ODL session. The items include the participants' perceived ease of use, perceived usefulness, attitude, and intention to use UiTM WESLLAP during ODL. The same set of questionnaires was distributed again to the same participants after ten weeks of ODL sessions using UiTM WESLLAP. The descriptive findings show increased positive perceptions of ODL by the participants after using the website. The study provides insights into the essential indicators of e-learning platform acceptance in a higher education institution, which can help in the enhancement of ODL platform for future development and implementation.